2010
DOI: 10.1088/0967-3334/32/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a novel superfusion system forex vivocharacterization of neural tissue by dielectric spectroscopy (DS)

Abstract: Dielectric spectroscopy is a widely utilized electrophysiological characterization method. The obtained dielectric spectra and derived properties have the potential of providing significant information regarding changes in the physiological state of a biological system. However, since many of the dielectric properties are obtained in vitro from excised tissue far removed from physiological conditions, the value of the information obtained may be diminished. In this paper, we introduce a superfusion system that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Dielectric spectroscopy, which has previously been shown to successfully probe the conductivity of polyelectrolyte solutions (Bordi et al 2004), was utilized to measure the complex conductivity of each solution sample. The electrode system has been previously described (Dobiszewski et al 2011) and shown to successfully measure conductivity. Briefly, the electrode system consisted of two 14 karat gold electrodes held parallel to one another at a precise distance apart.…”
Section: Conductivity Measurements and Analysismentioning
confidence: 99%
“…Dielectric spectroscopy, which has previously been shown to successfully probe the conductivity of polyelectrolyte solutions (Bordi et al 2004), was utilized to measure the complex conductivity of each solution sample. The electrode system has been previously described (Dobiszewski et al 2011) and shown to successfully measure conductivity. Briefly, the electrode system consisted of two 14 karat gold electrodes held parallel to one another at a precise distance apart.…”
Section: Conductivity Measurements and Analysismentioning
confidence: 99%